Stability of bifidobacteria entrapped in goat's whey freeze concentrate and inulin as wall materials and powder properties. (January 2020) - de Liz, Gabriela Rodrigues; Verruck, Silvani; Canella, Maria Helena Machado; Dantas, Adriana; Garcia, Sofia Grechi; Maran, Bruna Marchesan; Murakami, Fabio Seigi; Prudencio, Elane Schwinden
Graphical abstract: Highlights: Goat's whey concentrate was an efficient wall material for bifidobacteria. The inulin amount was not able to improve the viability of bifidobacteria entrapped. Goat's whey concentrate and inulin increased the thermal stability of microcapsules. Bifidobacteria survival decreased after the spray drying process. Abstract: Goat's whey was submitted to two cycles of block freeze concentration process, resulting in concentrate 1 and concentrate 2. Concentrate 1 was added with 5 g of inulin and both concentrates were inoculated with Bifidobacterium animalis ssp. lactis BB-12, the concentrates were then denoted as feed solutions 1 and 2, respectively. Feed solutions were spray-dried, resulting in powder 1 and 2. The stability of the bifidobacteria entrapped within the powders was evaluated for both spray-dried powders stored at 4 °C and 25 °C for 60 days. The spray-dried powders were also evaluated in relation to their physical and thermal properties. It was noted that Bifidobacteria displayed increased stability at refrigeration temperature. Analysis of physical properties indicated that the addition of inulin resulted in increased water solubility. However, both spray-dried powders displayed less flowability, as well as a yellow-greenish color. By evaluating the spray-dried powders thermal properties, it was possible to confirm that goat whey concentrates behave as excellent wall materials.